2005
DOI: 10.1103/physreva.72.043816
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of multisoliton formation and soliton energy quantization in passively mode-locked fiber lasers

Abstract: We report results of numerical simulations on the multiple soliton generation and soliton energy quantization in a soliton fiber ring laser passively mode-locked by using the nonlinear polarization rotation technique. We found numerically that the formation of multiple solitons in the laser is caused by a peak power limiting effect of the laser cavity.It is also the same effect that suppresses the soliton pulse collapse, an intrinsic feature of solitons propagating in the gain media, and makes the solitons sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
356
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 650 publications
(379 citation statements)
references
References 41 publications
21
356
1
1
Order By: Relevance
“…To assure large net positive cavity dispersion we also added a long piece of DCF to the cavity. In addition, we deliberately introduced large cavity birefringence in the laser, which strengthens the effect of the artificial birefringence filter formed in the cavity 17,18 .…”
Section: Experimental Studiesmentioning
confidence: 99%
“…To assure large net positive cavity dispersion we also added a long piece of DCF to the cavity. In addition, we deliberately introduced large cavity birefringence in the laser, which strengthens the effect of the artificial birefringence filter formed in the cavity 17,18 .…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Therefore increasing the gain of the laser cannot change the soliton parameters but increases the gain for the dispersive waves. When the dispersive waves become strong, they are shaped into a new soliton [5]. In fact, independent of the sign of the cavity GVD, in the lasers that are mode locked with the nonlinear polarization rotation technique the cavity pulse peak clamp effect always exists.…”
mentioning
confidence: 99%
“…The mechanism of multiple soliton formation in these lasers is due to the cavity pulse peak clamping effect [5]. A soliton formed in the laser has fixed energy.…”
mentioning
confidence: 99%
“…Passively mode-locked fiber lasers operating in the anomalous group-velocity dispersion (GVD) regime have been intensively investigated. [1][2][3][4] It was shown that, because of the natural balance between the cavity GVD and the fiber nonlinear optical Kerr effect, optical solitons are routinely produced in the lasers. Soliton operation of a laser could not only significantly narrow the mode-locking pulse width but also enhance the stability of the mode-locked pulses.…”
mentioning
confidence: 99%